2022
DOI: 10.1186/s12887-022-03115-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID-19 lockdown on the glycemic control of children with type 1 diabetes

Abstract: Background Between March 18th and May 13th 2020, the COVID-19 pandemic outbreak in Finland resulted in the closure of schools and the limitation of daycare (i.e. lockdown). Social distancing changed the daily routines of children with type 1 diabetes (T1D). Healthcare professionals were forced to adapt to the pandemic by replacing physical outpatient visits with virtual visits. However, the influence of the lockdown on glycemic control in these patients remained unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…These data were confirmed in several other studies around the world [80,81]. The same conclusion was reached in different studies with children with T1DM, where the glycemic control did not deteriorate under the lockdown [82,83]. There are even studies showing an improvement in the glycemic control in T1DM children during confinement [84].…”
Section: Lockdown and Its Effect On Diabetessupporting
confidence: 80%
“…These data were confirmed in several other studies around the world [80,81]. The same conclusion was reached in different studies with children with T1DM, where the glycemic control did not deteriorate under the lockdown [82,83]. There are even studies showing an improvement in the glycemic control in T1DM children during confinement [84].…”
Section: Lockdown and Its Effect On Diabetessupporting
confidence: 80%
“…Although the trends in recently published research are inconsistent, the majority indicated no deterioration or even an improvement in the management of T1DM patients during the COVID-19 pandemic [13,[19][20][21][22][23]. It is believed that telemedicine visits, use of advanced diabetes technologies (CGM, FGM, hybrid close loop), and improved self-care, as well as parental involvement, significantly contributed to better glycaemic control [15,24].…”
Section: Discussionmentioning
confidence: 99%
“…A slight but significant improvement was found in many glucose metrics, during the lockdown period, with both treatments, thanks to telemedicine. In another study from Finland, conducted in children patients treated with insulin pumps, an improvement of their glucose control, showing in particular, significant amelioration of TIR and mean glucose values, was demonstrated during the lockdown, with respect to the pre-lockdown period [ 60 ]. T1D adults using the most sophisticated therapeutical approach, i.e.…”
Section: Telemedicine and Diabetes Management During Covid-19mentioning
confidence: 99%